WHEN ENOUGH IS ENOUGH: AN UNNOTICED TELESTICH IN HORACE (SATIRES 1.4.14–18). (8th November 2018) - Fredericksen, Erik
Abstract : In these lines from the fourth poem of his first collection of satires (1.4.9–18), Horace defines his poetic identity against the figures of his satiric predecessor Lucilius and his contemporary Stoic rival Crispinus. Horace emerges as the poet of Callimachean restraint and well-crafted writing in contrast to the chatty, unpolished prolixity of both Lucilius and Crispinus. A proponent of the highly wrought miniature over the sprawling scale of Lucilius, Horace knows when enough is enough. And, owing to a playful link between what is satis ('enough') and satura ('satire'), this makes Horace not only a skilful poet but also the consummate sat irist. I suggest that this programmatic message is both emphasized and illustrated by a piece of wordplay beginning in line 14. In a previously unnoticed telestich, the last letters of lines 14–18 spell out the word satis ('enough'). Moreover, this hidden word—made possible only by the particular arrangement of words in all five of its lines—anticipates and deepens the poem's later interest in the matter of compositio, or artful word-arrangement. While this may be unique as an example of a Horatian telestich, Horace does engage in various forms of wordplay elsewhere, and could look not only to Hellenistic poets but also to Lucretius as a predecessor in this regard. In the Satires, a collection in which problems of libertas make forms of implication and veiled speech especially significant, a wide range of hidden words and wordplay has been detected and suggested. The instance observed here reaffirms Horace's interest in wordplay, while its uniqueness as a telestich is, as I hope to show, particularly suited to its context in this poem.